Genome-specific differential gene expressions in resynthesized Brassica allotetraploids from pair-wise crosses of three cultivated diploids revealed by RNA-seq - Zhang, Dawei; Pan, Qi; Cui, Cheng; Tan, Chen; Ge, Xianhong; Shao, Yujiao; Li, Zaiyun (Frontiers in Plant Science, 2015)
Polyploidy is popular for the speciation of angiosperms but the initial stage of allopolyploidization resulting from interspecific hybridization and genome duplication is associated with different extents of changes in genome structure and gene expressions. Herein, the transcriptomes detected by RNA-seq in resynthesized Brassica allotetraploids (Brassica juncea, AABB; B. napus, AACC; B. carinata, BBCC) from the pair-wise crosses of the same three diploids (B. rapa, AA; B. nigra, BB; B. oleracea, CC) were compared to reveal the patterns of gene expressions from progenitor genomes and the effects of different types of genome combinations and cytoplasm, upon the genome merger and duplication. From transcriptomic analyses for leaves and silique walls, extensive expression alterations were revealed in these resynthesized allotetraploids relative to their diploid progenitors, as well as during the transition from vegetative to reproductive development, for differential and transgressive gene expressions were variable in numbers and functions. Genes involved in glucosinolates and DNA methylation were transgressively up-regulated among most samples, suggesting that gene expression regulation was immediately established after allopolyploidization. The expression of ribosomal protein genes was also tissue-specific and showed a similar expression hierarchy of rRNA genes. The balance between the co-up and co-down regulation was observed between reciprocal B. napus with different types of the cytoplasm. Our results suggested that gene expression changes occurred after initial genome merger and such profound alterations might enhance the growth vigor and adaptability of Brassica allotetraploids.